TEACHING MATERIALS IN THE TEXTBOOK ENTITLED, “WHEN ENGLISH RINGS THE BELL” FOR JUNIOR HIGH SCHOOL STUDENTS YEAR VII - Rosi Kumala Sari (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
This study was a descriptive study aimed at describing the the quality of the textbook entitled, “When English Rings The Bell” for Junior High School Students Year VII in providing English teaching material to improve students’ English Knowledge competence.The researcher analyse this book based on the theory from Howard and Major (2010) about good teaching material in English language teaching. The subject of this study is the textbook entitled, “When English Rings The Bell” for Junior High School Students Year VII”. The sources of data of this study were collected by questionnaire and interview from respondents. The respondents were one english teachers from SMP 1 Padang and SMP 31 Padang. The result of this study showed that the respondents had same perception that the quality of the textbook entitled, “When English Rings The Bell” for Junior High School Students Year VII was poor in providing the English Teaching Material to improve students’ knowledge about WH questions.